Insecticidal efficacy and toxicity of petroleum ether extracts of some medicinal plants against adults of the red flour beetle Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) - رحمة حسن عمر الدليمي; هدى محمود علي إسماعيل (African Journal of Advanced Pure and Applied Sciences, 2025)
This study aimed to investigate the insecticidal efficacy and toxicity of petroleum ether extracts from four medicinal plants: leaves of Artemisia vulgaris L., flower buds of Syzygium aromaticum L., fruits of Capsicum annuum L., and fruits of Acacia nilotica L. against adults of the red beetle flour Tribolium castaneum (Herbst) at different exposure periods (24 hours, 48 hours, and 7 days). The results indicated that all plant extracts exhibited significant insecticidal activity against the adult beetle, effectively influencing mortality rates. This efficacy was enhanced with increasing concentration and exposure duration, indicating a cumulative and progressive effect of the active compounds in these extracts over time. Furthermore, distinct variations in insecticidal potency were observed among the different extracts. The petroleum ether extract of S. aromaticum L. displayed the highest insecticidal efficacy, achieving mortality rates of 76.67% at a 2.0% concentration after 24 hours, which increased to 100% after 7 days of treatment. This was followed by the A. vulgaris L. extract, which yielded high mortality rates of 96.67% and 100% at concentrations 1.0% and 2.0%, respectively, after 7 days. The C. annuum L. extract demonstrated a moderate, time-dependent efficacy, reaching a mortality rate of 86.7% at the highest concentration 2.0% after 7 days. In contrast, the A. nilotica L. extract was the least effective, with a mortality rate not exceeding 63.3% at the highest concentration after 7 days. Additionally, these extracts exhibited marked toxicity against the adult beetles, as quantified by the calculated LC50 and LC90 values across different exposure periods. The toxic efficacy varied considerably depending on the extract type, The S. aromaticum was the most toxic, followed by A. vulgaris L. then the C. annuum L. extract, while the A. nilotica L. was the least toxic. Toxicity of all extracts increased with extended exposure duration, as evidenced by the progressive reduction in LC50 and LC90 values after 48 hours and 7 days of treatment.